ANALYSIS OF BEHAVIORAL FINANCE IN STOCK INVESTMENT OF SAM RATULANGI UNIVERSITY STUDENT - Senewe, Virginia .; Lapian, S.L.H.V Joyce; Tumbuan, Willem J.F.A (Universitas Sam Ratulangi, 2018)
Abstract: Â Behavioral finance is a field ofÂ financeÂ that proposes psychology-based theories to explainÂ stock market anomaliesÂ such as severe rises or falls in stock price. Stocks are an equity investment that represents part ownership in a corporation and entitles you to part of that corporations earnings and assets. This study was conducted to test whether investors in the capital market Indonesia is always rational, with students being subject as representatives of academics who invest in capital markets, then it is hoped the subject has a better knowledge of investment in capital market. The method used in this research is qualitative to examine the experience of every individuals. The population in this study consisted of student of Sam Ratulangi University. The results showed that all the informants had the same experience when going to invest. They all had a fear to not getting a profit and losing their money. In truth, they want more beneï¬ts from their investments as they want from almost all products and services. BEI have to introduce more about them to students and other people in addition to know BEI and provide an opportunity for them to become investors and get profit from being the investor itself.Keywords: behavioural finance, stock investment, investor behaviour, investor psychology